(untitled) (La U Investiga, 2019)
The recovery of the hospitalized patient depends on the dietary therapy intervention and the food service is responsible for this, but your opinion as a user is also key to evaluating the quality of the service. This study determined the level of satisfaction of hospitalized patients regarding the diet provided by the Nutrition and Dietetics Service of the Hospital San Vicente de Paúl (HSVP) in Ibarra, 2018. It was a descriptive cross-sectional study in 200 patients, The Acute Care Hospital Foodservice Patient Satisfaction Questionnaire was adapted, and sociodemographic and hospital data were also collected. 61.5% were women; age 46.5 ± 12.1 years; hospital stay <1 week in 82.5%; 56.5% received a therapeutic diet and 82% received no prior information on the type of diet. 88% of those studied rated the food and distribution service as very good and good, as well as the taste of the food (85%), variety (83%), cooking and presentation (87%), temperature (76%), hours (71.5%), quantity (72%) and dishes (82.5%) were very good and good. The flavor, variety, presentation, temperature and quantity were significantly related to the final appreciation of food and service (p<0.05), but not the type of diet (p = 0.197) and occupation (p = 0.071). It is concluded that the level of satisfaction of hospitalized patients regarding the diet provided by the HSVP Nutrition and Dietetics Service, in the period studied was very good and good, however, meal times should be improved.